Nanoplastics induces arrhythmia in human stem-cells derived cardiomyocytes - Shirley Pei Shan Chia; Jeremy Kah Sheng Pang; Winanto Winanto; Boon-Seng Soh (Ecotoxicology and Environmental Safety)
Nanoplastics (NPs), plastic particles ranging from 1–1000 nm, form through weathering and are considered more hazardous than larger plastics due to their ability to penetrate cell barriers and be internalised by biological systems. Most research on NPs has focused on animal models, examining effects on the brain, lungs, and gastrointestinal tract. To enhance physiological relevance, this study investigated the impact of NPs on human cardiomyocytes (CMs) derived from human embryonic stem cells (hESCs). We observed significantly higher cellular uptake of 50 nm NPs compared to 500 nm particles, with dose-dependent accumulation over 3, 5, and 7 days of treatment. This accumulation induced oxidative and endoplasmic reticulum (ER) stress, culminating in arrhythmias by day 7. Complementing these in vitro findings, transcriptome profiling of mice exposed to NPs for 8 weeks revealed disrupted RNA splicing, dysregulated protein translation, and defective protein folding. These molecular changes led to ER stress, apoptosis, and impaired transmembrane ion conductance, contributing to the arrhythmic phenotype. Our findings highlight the detrimental effects of NPs on the human heart. Further research is needed to fully elucidate the mechanisms underlying NP-induced toxicity and to develop strategies for mitigating their adverse effects. This study underscores the urgency of addressing NP pollution to protect human health.